Lignite planning, structural change and coal phase-out in Germany - Andreas Berkner; Gesa Dähnhardt; Jan Falke; Angiola König; Kerstin Kynast; Karina Lüdenbach; Vera Müller; Alexandra Renz; Marion Schilling; Michael Sehrig; Tobias Thieme; Thomas Tschetschorke; et al. (Verlag der ARL - Akademie für Raumentwicklung in der Leibniz-Gemeinschaft, 2022)
Lignite planning in the Rhineland, central German and Lusatian coalfields is a core spatial development planning task at the federal state and regional levels. The Lignite Planning Information Group and Initiative (Informations- und Initiativkreis Braunkohlenplanung) was founded in 1994 at the ARL - Academy for Territorial Development in the Leibniz Association to provide a platform for expert discussion. Starting from experiences with the Rhineland and the structural upheavals in the new federal states in the early 1990s, it has since continuously addressed new technical and legal requirements involving resettlement, water balance issues, environmental assessments, the energy transition and the common good. Against the backdrop of rapid change and geopolitical events, the combination of structural change and the politically initiated phase-out of lignite-based power generation in a time frame between 'ideally 2030' and no later than the end of 2038 constitutes a challenge that will have to be met by the active players from the perspective of both federal state and regional planning and of regional development. This position paper takes stock of the situation across federal states and across coalfields and describes the required actions for lignite planning as a basis for reaching conclusions about a process with far-reaching national consequences. The various aspects of this process are subject to constant change and call for proactive strategies to exploit opportunities, tap potential, and effectively identify and avoid negative developments.
urn:nbn:de:0156-01403
Keywords: 710